1988
DOI: 10.1111/j.1439-0442.1988.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Insulin on Abomasal Emptying in Cattle*

Abstract: The influence of glycaemic status and blood insulin levels on abomasal emptying rate was Endogenous insulin, secreted after i. v. glucose infusion, as well as exogenous injected insulin, It is suggested that insulin itself, apart from hyperor hypoglycaemia, might be the major cause studied in 4 fistulated heifers.caused a marked decrease of abomasal emptying rate lasting several hours. of inhibition of abomasal emptying, acting either centrally or peripherally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Increased insulin was observed in cases with DA (Van Meirhaeghe et al, 1988b;Pravettoni et al, 2004;Sen et al, 2006) and was implicated as a factor in the pathogenesis of DA (Van Meirhaeghe et al, 1988b;Geishauser, 1995). Van Meirhaeghe et al (1988a) observed decreases in abomasal emptying after an intravenous glucose infusion, followed by an increased secretion of endogenous insulin. The same observation was made after a bolus injection of exogenous insulin, which was followed by a decrease in plasma glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Increased insulin was observed in cases with DA (Van Meirhaeghe et al, 1988b;Pravettoni et al, 2004;Sen et al, 2006) and was implicated as a factor in the pathogenesis of DA (Van Meirhaeghe et al, 1988b;Geishauser, 1995). Van Meirhaeghe et al (1988a) observed decreases in abomasal emptying after an intravenous glucose infusion, followed by an increased secretion of endogenous insulin. The same observation was made after a bolus injection of exogenous insulin, which was followed by a decrease in plasma glucose.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the tissues are insensitive to insulin with regard to uptake of glucose, which points to insulin resistance. It has been postulated that high insulin levels could play a role in the pathogenesis of abomasal displacement (23).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the degree of energy deficiency and especially on the preparturient fat status of the animal, the amount of fat droplets in the hepatocytes can be so high that it interferes with normal liver cell function (13). Abomasal displacement, besides other complications as chronic ketosis, parturient paresis, retained placenta and endometritis, has often been associated with a fatty liver (3,5,20,23).…”
Section: Introductionmentioning
confidence: 99%
“…1 Medical treatment of cattle suspected to have abomasal hypomotility is widely practiced, but few data are available on treatment efficacy. 2 Because abomasal hypomotility has been associated with hypocalcaemia, 3,4 endotoxemia, 5 alkalemia, 6 hyperinsulinemia, 7 and hyperglycemia, 8,9 the current focus of treatment of adult cattle and calves suspected to have abomasal hypomotility is correction of acidbase, electrolyte, and metabolic abnormalities; amelioration of the effects of endotoxemia; and elimination of gram-negative bacterial infections. Some clinicians also administer neostigmine, metoclopramide, or erythromycin to ruminants suspected to have abomasal hypomotility, on the basis of evidence to suggest that these medications have a prokinetic effect in neonatal 10 and adult humans 11 and domestic monogastric animals.…”
mentioning
confidence: 99%